Infertility and mental disorders in women. Communication 1 - N. A. Tyuvina; A. O. Nikolaevskaya (Неврология, нейропсихиатрия, психосоматика, 2019)
This paper presents the definition, epidemiology, etiological factors, and approaches to classifying infertility and describes the relationship between mental health and infertility in women. The problem of idiopathic infertility is analyzed from both obstetric/gynecological and psychiatric positions. The psychological factors influencing the reproductive function of a woman are disclosed. Mental health disorders potentiating infertility are considered. Attention is paid to that mental disorders are insufficiently and untimely diagnosed in women with reproductive disorders, that certain forms of psychopathology are masked by functional gynecological disorders, and that obstetricians/gynecologists have no specialized ideas of women's mental health, which may lead to unsuccessful infertility therapy.